Design leadership : how top design leaders build and grow successful organizations - Banfield, Richard (O'Reilly Media, 2015)
"What does it take to be the leader of a design firm or group? We often assume they have all the answers, but in this rapidly evolving industry they're forced to find their way like the rest of us. So how do good design leaders manage? If you lead a design group, or want to understand the people who do, this insightful book explores behind-the-scenes strategies and tactics from leaders of top design companies throughout North America."--provided from Amazon.com.